Student Strategies for Coping with Textbook Costs and the Role of Library Course Reserves - Middleton, Cheryl; Christie, Anne; Pollitz, John H. (My University, 2009)
College and university students across the United States are concerned about the cost of textbooks. This study examines the student patterns of coping with textbook inflation and the role that course reserve collections play in ameliorating costs. In the winter of 2007, an online survey was distributed to 1,500 Oregon State University students to explore their textbook purchasing habits and use of course reserves. Students reported that textbook costs come directly from their personal funds. They see course reserves as one mechanism to help them deal with textbook costs. Libraries could focus efforts to assist students by purchasing recommended and optional textbooks.
Keywords: Textbooks, Economic aspects; Library resources; Libraries & textbooks; College textbooks; Library surveys